Study and Evaluation of bricks made from the local sand using sodium silicate as binder - Mohammed Ali Jaber, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
In this study, a mixture of (sand and sodium silicate (ratio 4:1) was composed , where sodium silicate is used as a binding agent, and put in an furnace at different temperatures ranging from (200-1000 0C). It was observed that the density and compressive strength with increasing temperature up to 800 0C degrees where the compressive strength at its maximum of 12 MPa. the effect of the waste glass used in the mixture was studied by adding different rates. It was observed that the density of the models increases with increased rates of waste glass, but at a temperature of 800 0 C noted that density decreases with the increase in the proportion of the mixture, while there was a clear increase in the strength of compression of the models with increased rates of waste glass . Also the process of sintering was studied was developed models that have the same ratio (sand (52%), waste glass (28%), sodium silicate (20%)) in an oven at a temperature of 800 were the physical properties (density, compressive strength and volume) with the change of time (4-20) hr the result show that the density decreases with increasing temperature and also increased volume. The compression strength, decreases with time but at 16 hr it reaches a maximum of more than( 6 MPa).